COMPUTATIONAL MODELLING AND PREDICTING SPREAD OF ARBOREAL EPIDEMIC - Rai, Ankush; R, Jagadeesh Kannan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
This study presents a modelling solution for the arboreal epidemic like Huanglongbing. Usually, the spread of such plant disease is modelled based upon the four parameters such as: susceptibility, exposure, infectiousness, detection and removed but such a model is deprived from the time as a dimension to model such variations. Owing to this the time for which infection, exposure, detection and removal time is censored form modelling studies of disease spread through heterogeneous plant species. The research presented in this work characterize such heterogeneous transmission with integration of temporal spatial modelling of latent period of season and effects on the host, infection period and dispersal parameters corresponding to the host age. The outcome form this research will enable to control arboreal epidemic.